1964
DOI: 10.1139/v64-417
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Syntheses: 9. The Conversion of Dibenzoylmethane to Tribenzoylethane

Abstract: Irradiation of dibenzoylmethane in benzene gives tribenzoylethane. In more concentrated solution a solid dimer (11) separates which, on solution, is converted by dealdolization into a n isomer. This isomer (I, R = H) on irradiation, gives tribenzoylethane in a photolytic reaction which has been shown t o have some generality. The overall conversion of dibenzoylmethane t o tribenzoylethane therefore involves two photochemical and one chemical reactions.Some time ago, as part of our studies on photochemical cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Previous studies revealed that the De Mayo reaction could occur spontaneously under light mediated conditions (UV and visible light). 9,17 However, it remains to be an interesting question whether this step is enzyme-or nonenzyme-catalyzed in the plant. Compounds 1 and 2 were evaluated for their antiinflammatory effects in vivo.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Previous studies revealed that the De Mayo reaction could occur spontaneously under light mediated conditions (UV and visible light). 9,17 However, it remains to be an interesting question whether this step is enzyme-or nonenzyme-catalyzed in the plant. Compounds 1 and 2 were evaluated for their antiinflammatory effects in vivo.…”
supporting
confidence: 83%
“…Subsequently, a retro-aldol reaction of the formed intermediates i or ii could lead to C8′–C9′ cleavage and produce compounds 1 and 2 . Notably, the intermediates i and ii are unstable due to the presence of the β-hydroxyketone moiety that could induce a retro-aldol process. , Thus, 1 and 2 were proposed to be formed by De Mayo reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The above-mentioned photoinitiators undergo a rapid ␣-cleavage (Norrish type I) from their excited triplet state. 19,20 The subsequent photochemical transformation of the resulting radicals pair, however, is quite different. The 1,1-dimethoxybenzyl radical from Irgacure 651 undergoes a secondary fragmentation reaction to yield the inactive methyl benzoate and the active methyl radical (Scheme 3).…”
Section: Methodsmentioning
confidence: 99%